2010
DOI: 10.1007/s11434-010-4192-2
|View full text |Cite
|
Sign up to set email alerts
|

First observation of mesospheric and thermospheric winds by a Fabry-Perot interferometer in China

Abstract: A Fabry-Perot interferometer, funded by the Meridian Project in China, was deployed at the Xinglong station (40. 2°N,117.4°E) of the National Astronomical Observatories in Hebei Province, China. The instrument has been operating since April 2010, measuring mesospheric and thermospheric winds. The first observational data of winds at three heights in the mesosphere and thermosphere were analyzed, demonstrating the capacity of this instrument to aid basic scientific research. The wavelengths of three airglow emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Nevertheless, Yuan et al (2010) reported a 4-month oscillation in their seasonal analysis of NmF2 ionosonde data from 33 stations at three different longitudes from 1969 to 1986. They also found a good phase match between annual and semiannual oscillations as well as for the terannual oscillation; on this basis they concluded that the terannual oscillation could be the response to a nonlinear interaction between annual and semiannual oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Yuan et al (2010) reported a 4-month oscillation in their seasonal analysis of NmF2 ionosonde data from 33 stations at three different longitudes from 1969 to 1986. They also found a good phase match between annual and semiannual oscillations as well as for the terannual oscillation; on this basis they concluded that the terannual oscillation could be the response to a nonlinear interaction between annual and semiannual oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed some preliminary studies based on the FPI data. Firstly, we compared the FPI winds during the period of 5 April-12 May 2010 with HWM93 (Yuan et al, 2010). Our comparisons showed that the winds from FPI agreed well with those from HWM93 at the altitudes of ∼ 87 and ∼ 98 km and exhibited apparent semidiurnal variations.…”
mentioning
confidence: 83%
“…Thus, the time resolution is ∼ 1 h (Jiang et al, 2012). From the interference patterns of airglow radiations, horizontal winds at the altitudes of ∼ 87, ∼ 98 and ∼ 250 km are derived with a time interval of ∼ 1 h. A detailed description of the FPI and data processing method can be found in Wu et al (2004) and Yuan et al (2010). Here, we concentrate on the distributions of the available wind data from April 2010 to July 2012.…”
Section: Instrument and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The FPI in Kelan observes at wavelength of OH 892.0, OI 557.7, and OI 630.0 nm to derive the nighttime wind and temperature at 87, 97, and 250 km, respectively, and is designed almost the same as the one in Xinglong (40.2 • N, 117.4 • E) [36]. More details of the mechanism can be found in Yu et al [30].…”
Section: Fpi Datamentioning
confidence: 99%